Tamne Yisan Kefase: Upaya Merawat Kerukunan Umat Beragama berbasis Kearifan Lokal di Kabupaten Keerom - Sumardi, Joseph; Kadir, Akhmad; Lekitoo, Hanro Y. (CENDERAWASIH: Jurnal Antropologi Papua, 2023)
This research aims to describe the general condition of religious harmony in Keerom Regency, which in recent years has been disturbed by the presence of several religious groups. Their presence can trigger religious conflicts in the community. The goal is expressed through local wisdom that serves to maintain religious harmony. This research uses a qualitative descriptive approach. The research location was in Keerom Regency. The technique of determining informants is done by snowball. The research instruments used are recording devices, interview guidelines and notebooks. Data collected using observation and interview techniques were then analyzed qualitatively. Data analysis went through the stages of data reduction, data presentation, data verification and conclusion drawing. The results showed that the condition of religious harmony in Keerom is generally in a safe level although there are some certain frictions, but not to cause major conflicts. Tamne Yisan Kefase (consensus to build together) is a motto taken from the local language which is full of meaning. The main principle of this motto is to work together. This value is then held and lived by every community that inhabits the Keerom region, including in religious matters. The local wisdom is carried out until now in order to maintain and care for religious harmony in Keerom Regency.